Comparison of Laparoscopic Intraperitoneal Onlay Mesh Repair (IPOM plus) vs Open Rives–Stoppa (RS) Repair for Ventral and Incisional Hernia - Havrylov , Hryhorii O.; Shulyarenko , Oleg V.; Yosypenko, Mykhaylo O. (Acta medica Lituanica, 2024)
Aim. To compare the effects of laparoscopic intraperitoneal onlay mesh plus repair versus open Rives–Stoppa repair for abdominal wall hernias.Materials and methods. A total of 99 patients with midline primary, umbilical or incisional hernias who underwent surgery in “Medikom” clinic and Kyiv city hospital #5 in the period from 2016 to 2022 were involved in the study. The group I included 50 patients who underwent intraperitoneal onlay mesh (IPOM) plus, and the group II 49 patients who underwent open Rives–Stoppa (RS) repair.Result. Both groups were comparable in mean age, gender, body mass index, patient distribution based on hernia type, defect size, ASA score distribution (p > 0.05).The operating time in minutes was 75.36 ± 4.99 in group I and 97.85 ± 6.5 in group II (p < 0.05). The blood loss in IPOM plus approach group is on average in 2 times less than in open RS technique (p < 0.05). The pain score 12 hours after surgery was 5.5 ± 0.64 in group I comparing to 7.26 ± 0.78 in group II (p < 0.05). The pain score 24 hours after surgery was 4.46 ± 0.7 in group I comparing to 4.95 ± 0.61 in group II (р < 0.05). The pain score 8 days after surgery in group I was on average in 1.46 times less than in group II (p < 0.05).No significant difference was found in incidence of early complications between two groups (p > 0.05).47 (94%) patients of group I and 46 (93.87%) patients of group II were evaluated over 22 months follow-up period. No one complication was noted.Conclusions. IPOM plus approach for the ventral and incisional hernias repair is a viable and relatively more safe operation by comparing with open RS repair. IPOM plus approach takes significantly in 1.3 less time as compared open RS technique.
Keywords: laparoscopy; hernia; mesh; surgery; ipom plus